Evolutionary dynamics and functional characterization of proximal duplicated sorbitol-6-phosphate dehydrogenase genes in Rosaceae - Yang, Fan; Luo, Jiawei; Han, Songxue; Zhang, Yirong; Liu, Zhiguang; Lan, Jincheng; Sun, Yaqiang; Zhao, Tao (Frontiers in Plant Science, 2024)
Sorbitol is a critical photosynthate and storage substance in the Rosaceae family. Sorbitol 6-phosphate dehydrogenase (S6PDH) functions as the pivotal rate-limiting enzyme in sorbitol synthesis. The origin and functional diversification of S6PDH in Rosaceae remain unclear, largely due to the complicated interplay of gene duplications. Here, we investigated the synteny relationships among all identified S6PDH genes in representative genomes within the Rosaceae family. By integrating phylogenetic analyses, we elucidated the lineage-specific expansion and syntenic conservation of S6PDH across diverse Rosaceae plant lineages. We found that S6PDH can be traced back to a pair of proximal duplicated genes of the common ancestor of the Rosaceae, and the further amplification of S6PDH in the Maleae primarily relies on WGD events in their lineages. In Rosaceae species, multiple copies of the S6PDH gene are preliminarily divided into two main clades (Clade 1 and Clade 2) based on sequence similarity. These clades have evolved to acquire different functional directions. In Clade 1, lineage-specific transposition events in the Amygdaloideae have led to changes in gene expression patterns and promoted lineage evolution. This is mainly characterized by a decrease in enzymatic activity and transcriptional expression in the leaves, but also includes specific functional diversification, such as sustained post-harvest fruit expression and enhanced expression under biotic stress in certain tissues. In contrast, S6PDH in the Rosoideae and Dryadoideae has not undergone additional duplications beyond early proximal duplication. The loss of exons and variations in exon length might the key factor leading to reduced enzymatic activity in the Clade 2 proximal gene pairs. Collectively, our findings illuminate the dynamic nature of S6PDH evolution and reveal the intricate interplay between duplication, transposition, and functional diversification. This work not only contributes valuable insights into the genetic mechanisms underlying sorbitol metabolism but also establish a crucial foundation for future investigations aimed at comprehensively characterizing the variations of sorbitol metabolism across different subfamilies within the Rosaceae family.